Leftward Deviation and Asymmetric Speed of Egocentric Judgment between Left and Right Visual Fields - Zhou, Ying; Li, Bing; Wang, Gang; Zhang, Mingsha; Pan, Yujun (Frontiers in Neuroscience, 2017)
The egocentric reference frame is essential for body orientation and spatial localization of external objects. Recent neuroimaging and lesion studies have revealed that the right hemisphere of humans may play a more dominant role in processing egocentric information than the left hemisphere. However, previous studies of egocentric discrimination mainly focused on assessing the accuracy of egocentric judgement, leaving its timing unexplored. In addition, most previous studies never monitored the subjects’ eye position during the experiments, so the influence of eye position on egocentric judgment could not be excluded. In the present study, we systematically assessed the processing of egocentric information in healthy human subjects by measuring the location of their visual subjective straight ahead (SSA) and their manual reaction time (RT) during fixation (monitored by eye tracker). In an egocentric discrimination task, subjects were required to judge the position of a visual cue relative to the subjective mid-sagittal plane and respond as quickly as possible. We found that the SSA of all subjects deviated to the left side of the body mid-sagittal plane. In addition, all subjects but one showed the longest RT at the location closest to the SSA; and in population, the RTs in the left visual field (VF) were longer than that in the right VF. These results might be due to the right hemisphere's dominant role in processing egocentric information, and its more prominent representation of the ipsilateral VF than that of the left hemisphere.